Degree of anaemia based on treatment period, type of OAT, and BTA status in intensive-phase pulmonary tuberculosis patients - Andini, Asfina; Aisah, Siti; Al Jihad, Much Nurkharistna; Soesanto, Edy (University of Muhammadiyah Semarang, 2024)
Pulmonary tuberculosis can cause anaemia. Anti-tuberculosis Medications (ATM) are divided into 2 types namely Fixed Dose Combination (FDC) and release. The intensive phase of ATM can cause side effects in mild, moderate, or severe anaemia. This study aims to describe the degree of anaemia in intensive-phase pulmonary TB patients based on the duration of treatment for ATM, type of ATM, and smear status. This research is a retrospective descriptive using secondary data in the form of medical records and the results of the Hb examination in the laboratory. The sampling technique used purposive sampling with inclusion criteria including drug-sensitive pulmonary TB, currently undergoing intensive phase treatment, experiencing anaemia based on the degree of anaemia according to WHO. Exclusion criteria included extrapulmonary TB, drug-resistant TB, and pregnant women. A total of 134 samples and data analysis using univariate analysis. Based on the degree of anaemia, the highest percentage of mild anaemia was during the 2nd week of treatment (60.9%), the type of ATM release (60.0%), and smear-positive (55.3%). The highest percentage of moderate anaemia was in the 6th week (100%), ATM FDC (43.6%), and smear-negative (48.4%). The highest percentage of severe anaemia was at week 8 (50.0%), ATM FDC (6.4%), and smear-negative (6.5%). Worsening of the degree of anaemia as the treatment period progresses, in patients with pulmonary TB who are taking FDC and are smear-negative.